Las tareas de aprendizaje en la iniciación al atletismo a través del modelo de enseñanza ludotécnico - Valero Valenzuela, Alfonso; Gómez López, Manuel (KRONOS, 2007)
It is described how, from the Ludotechnic Instructional Pattern for Track and Field in beginners, teachers show the students what they are supposed to learn, the task presentation and when it is the right moment to change to the following one. In the fi rst stage the previous knowledge of the students is connected with tasks list to be introduced, besides of generating a mental disorder that takes them to signifi cant learning by themselves. In Ludotechnic Pattern some of the parts in which the athletic discipline has been splitted is included, trying students to acquire basic movement schemes in a enjoyable and fun environment. Holistic patterns use the whole of each athletic technique, combining what has been learned before with nearer to the sport situations. In the last part, teacher and students answer questions and doubts arising from the lesson. Kids motivation engagement with learning tasks means tasks list progression criteria, thinking on motor learning and control skills from a more cognitive and global perspective, connected to current school pedagogical system.